AlMe3‐Mediated Regio‐ and Chemoselective Reactions of Indole with Carbamoyl Electrophiles. Issue 15 (2nd April 2013) - Velavan, A.; Sumathi, S.; Balasubramanian, K. K.
Abstract: Herein, we report the regio‐ and chemoselective reactions of indole with carbamoyl electrophiles in presence of AlMe3 . Indole‐3‐carboxamide was prepared in one‐step from a reaction of indole with tertiary carbamoylimidazole in the presence AlMe3 . Under conditions for the formation of an aluminium ate complex, the reaction was diverted to the indole nitrogen. Secondary carbamoyl electrophiles in the presence of AlMe3 regiospecifically yielded trisubstituted ureas. The regiospecificity and chemoselectivity of the indole nitrogen towards ester and tertiary carbamoylimidazole functionalities were also studied. Abstract : The regioselective one‐step synthesis of indole‐3‐carboxamide was achieved from the reaction between indole and a tertiary carbamoylimidazole in the presence of AlMe3 . Alternatively the reaction was diverted to the indole nitrogen when an aluminium ate complex was employed. Secondary carbamoyl electrophiles in the presence of AlMe3 exclusively yielded trisubstituted ureas.